Detection of numerical chromosome aberrations in bladder cancer by in situ hybridization. - Hopman, A. H. (1989)
The nuclear DNA content of 53 transitional cell carcinomas (TCCs) of the urinary bladder, as determined by flow cytometry (FCM), was compared with chromosome ploidy as detected by nonradioactive in situ hybridization (ISH). For this purpose, probes for repetitive DNA targets in the (peri) centromeric region of chromosomes 1 and 18 were used. Hybridization results with both probes of 35 TCCs, which had a DNA index of approximately 1.0 as concluded from FCM, showed evident chromosome 1 aberrations in approximately 25% of the tumors, and in a few cases an aberration for chromosome 18 was detected. Comparison of the ISH spot numbers for both chromosomes showed in most cases a higher number for chromosome 1 than for chromosome 18. ISH on 18 cases of TCCs, which showed a single peak in FCM with a DNA-index of 1.2 to 3.2, exhibited a profound heterogeneity. In these TCCs the ratio between chromosomes 1 and 18 varied over a wide range, resulting in cases showing more hybridization signals for chromosome 1 than for chromosome 18 or the opposite. Furthermore, using ISH minor cell populations showing polyploidization and giant cells containing numerous ISH signals could occasionally be detected. Results showed that interphase cytogenetics by ISH enable a fast screening of numerical chromosome aberrations and detection of different cell populations within one tumor, which was apparently homogeneous according to FCM.